2016
DOI: 10.1007/s00330-016-4508-y
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of combined use of contrast-enhanced ultrasound and TI-RADS classification for the differentiation of benign from malignant lesions of thyroid nodules

Abstract: PurposeTo study the thyroid image reporting and data system (TI-RADS) classification and the contrast-enhanced ultrasound (CEUS) enhancement pattern of thyroid nodules, and to determine whether combined use of both methods is helpful in the diagnosis of thyroid nodules.MethodsA total of 319 thyroid nodules in 246 patients were assessed with TI-RADS, CEUS and a combination of both methods. The diagnostic performance of TI-RADS, CEUS and a combination of both methods was compared.ResultsThe accuracy in the diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 14 publications
6
68
0
1
Order By: Relevance
“…Contrast‐enhanced ultrasound (CEUS), as one of the novel US modalities, could provide much better characterization of dynamic microvessel perfusion in the differential diagnosis of focal thyroid nodules than conventional US . However, to our knowledge, no studies have reported the CEUS features of mummified thyroid nodules and their differences from papillary thyroid carcinomas (PTCs).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Contrast‐enhanced ultrasound (CEUS), as one of the novel US modalities, could provide much better characterization of dynamic microvessel perfusion in the differential diagnosis of focal thyroid nodules than conventional US . However, to our knowledge, no studies have reported the CEUS features of mummified thyroid nodules and their differences from papillary thyroid carcinomas (PTCs).…”
mentioning
confidence: 99%
“…Contrast-enhanced ultrasound (CEUS), as one of the novel US modalities, could provide much better characterization of dynamic microvessel perfusion in the differential diagnosis of focal thyroid nodules than conventional US. 8,9 However, to our knowledge, no studies have reported the CEUS features of mummified thyroid nodules and their differences from papillary thyroid carcinomas (PTCs). The purpose of our study was to highlight the grayscale, color Doppler, and contrastenhanced US features of mummified thyroid nodules, which should help differentiate them from histologically proven PTCs.…”
mentioning
confidence: 99%
“…When CEUS was initiated, the imaging section was maintained unchanged for each patient (13). Dynamic contrast images underwent successive or frame-by-frame playback and the CEUS diagnostic criteria were divided into peak enhancement (hypo-enhancement, iso-enhancement and hyper-enhancement), homogeneity of enhancement (interior solid portion of target nodules, classified as homogeneous or heterogeneous) and rim-like enhancement (14). For obtaining degrees of echo and enhancement of nodules, CEUS findings were compared with adjacent muscles or normal thyroid parenchyma.…”
Section: Conventional Us /Ceus Examination and Image Analysismentioning
confidence: 99%
“…The malignant thyroid nodules were diagnosed based on inhomogeneous low enhancement in nodule tissues. The diagnostic criteria for benign thyroid nodules were the opposite of malignancy, including high enhancement or equal enhancement, and presence of rim-like enhancement in nodule tissues (14).…”
Section: Conventional Us /Ceus Examination and Image Analysismentioning
confidence: 99%
“…Although the diagnostic accuracy of ES alone is not optimal, the information it supplies is useful when combined with that obtained via other US techniques (16). These advanced integrative techniques reportedly improved the diagnostic accuracy of the thyroid image reporting and data Differential diagnosis of thyroid nodules through a combination of multiple ultrasonography techniques: A decision-tree model system (TI-RADS) (17). However, to the best of our knowledge, no previous study has provided a systematic method for integrating US parameters from multiple techniques; physicians and sonographers are sometimes overwhelmed by the large amount of information acquired (18).…”
Section: Introductionmentioning
confidence: 99%